Skewing Technology for Permanent Magnet Synchronous Motors: A Comprehensive Review and Recent Trends - Ren Tsunata; Masatsugu Takemoto (IEEE Open Journal of the Industrial Electronics Society)
This article gives a comprehensive overview of the current research trends in the skewing technique for permanent magnet synchronous motors (PMSMs). The skewing technique has been widely used in many applications to reduce the cogging torque and torque ripple in PMSMs. There are many ways to implement the skew, and new techniques are continually being developed. First, this article summarizes the types of skew structures and presents a survey of existing techniques. Specific emphasis is placed on what kind of skew structure is selected depending on the PMSM configuration. Second, the optimal value of the skew angle for each structure is comprehensively explained, and the discrepancy between theory and finite element analysis is discussed. The definition of skew angle varies across the literature, and one of the purposes of this article is to organize the definition in an easy-to-understand manner. In addition, this article offers three-dimensional finite element analysis (3D-FEA) results of various PMSMs employing the skew for quantitative comparison. Then, this article discusses the properties of PMSMs using the skew by structure and the latest trends, and finally describes future prospects.